Under the Leadership of the Communist Party of Czechoslovakia towards fresh victories of socialism - towards communism. Speech at the special session of the Central Committee of the Communist Party of Czechoslovakia on May 13, 1961 ([N.pl.)
Fortieth anniversary of the foundation of the Communist Party of Czechoslovakia.